Impact of GSTM1, GSTT1 and GSTP1 genes polymorphisms on clinical toxicities and response to concomitant chemoradiotherapy in cervical cancer. Issue 4 (2nd October 2018) - Abbas, M; Kushwaha, VS; Srivastava, K; Raza, ST; Banerjee, M
ABSTRACT: Background : Certain forms of chemoradiotherapy generate toxic reactive oxygen species, which may be ameliorated by antioxidant enzymes such as glutathione S-transferase (GST). Genetic polymorphisms of GST may predict treatment outcomes and can be used as genetic marker to screen patients before treatment. We hypothesised an effect of GST polymorphisms on the response and toxicities produced by chemoradiation therapy. Materials and methods : GST polymorphisms were determined by multiplex polymerase chain reaction and PCR-restriction fragment length polymorphism (PCR-RFLP) in 227 women with cervical cancer receiving cisplatin based chemoradiotherapy. Treatment response and toxicities were evaluated by standard internationally recognised criteria (RECIST and RTOG). Results : Severe (grade 3–4) gastrointestinal and haematological toxicities were present in 22 (9.4%) and 16 (7.0%) patients, respectively. GSTM1 null, GSTT1 null and GSTP1 AG genotypes brought marginally better non-significant associations. In single locus analysis GSTP1 AG and GG was linked to greatest risk of severe (grade 3–4) gastrointestinal toxicity (OR = 3.12, P = 0.035 and OR = 6.99, P = 0.01, respectively). In gene–gene interaction analysis, GSTM1 null- GSTP1 GG showed 4.2-fold higher risk of severe gastrointestinal toxicity ( P = 0.014). GSTT1 null- GSTP1 AG reached statistical significance with a 3.9-fold higher risk of high grade gastrointestinal toxicity ( P = 0.038). Conclusions : Although no significant links were found between GST polymorphism and treatment response, null genotypes of GSTM1, GSTT1 and 'G' allele of GSTP1 bring a higher risk of severe gastrointestinal toxicity due to chemoradiation therapy in cervical cancer.